Rekonfigurasi Jaringan Distribusi Radial Menggunakan Modified Firefly Algorithms (MFA) Pada Penyulang Tanjung Rayon Jombang - Hidayatul Nurohmah; Agus Raikhani; Machrus Ali (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2017)
Reconfiguring a distribution network is necessary to reduce power loss and increase system reliability.Different distribution forms will affect the large power losses so that it is necessary to reset the network configuration.Reconfiguration is done by opening and closing switches on the best distribution network.The amount of feeder and bus on the network will be difficult and require a very long time if calculated manually.The repeater of Tanjung Rayon Jombang consists of 41 Buses and 44 feeders.Therefore it is necessary to solve the problem by using artificial intelligence or Artificial Intelligent (AI).Firefly Algorithms (FA) widely used research in solving the optimization problem.Modified Firefly Algorithms (MFA) is an FA modification designed to solve discrete combination optimization problems.MFAs can search for the best network reconfiguration so that it can reduce 12,0866 kWatt or 12,6881% in Cape repeater.With the end voltage before reconfiguration 0.92959 pu to 0.94072 pu.This method can later use other artificial intelligence or can be applied to other repeater, thus reducing the losses of electrical energy.